1997
DOI: 10.3171/jns.1997.87.5.0716
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin B and middle cerebral artery occlusion in the rat

Abstract: Lysosomal proteases, although tightly regulated under physiological conditions, are known to contribute to cell injury after various forms of tissue ischemia have occurred. Because cathepsin B is a prominent lysosomal protease found in brain parenchyma, the authors hypothesized that it may contribute to neuronal cell death after focal cerebral ischemia. The authors measured the expression and spatial distribution of cathepsin B within the ischemic brain in 43 animals by means of immunohistochemical analysis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 34 publications
(16 reference statements)
5
48
0
Order By: Relevance
“…Previously, we have shown that cathepsin B undergoes increased expression and activation in core neurons early after reperfusion following MCAO in the rat [11]. We now provide new data to show that the enzymatic activity of cathepsin B is elevated predominantly in the right subcortical region of the ischemic brain where the level of several ~66 kDa proteins were found to increase significantly after the ischemic insult.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Previously, we have shown that cathepsin B undergoes increased expression and activation in core neurons early after reperfusion following MCAO in the rat [11]. We now provide new data to show that the enzymatic activity of cathepsin B is elevated predominantly in the right subcortical region of the ischemic brain where the level of several ~66 kDa proteins were found to increase significantly after the ischemic insult.…”
Section: Discussionsupporting
confidence: 51%
“…Such a critical pathway is the rapid activation of cysteine proteases including the cathepsins, calpains, and caspases [4][5][6][7][8]. Cathepsins B and L contribute to cerebral injury after focal ischemia with reperfusion [9][10][11][12][13]. Previously, we demonstrated that CP-1, a non-toxic cysteine protease inhibitor which is relatively selective for cathepsins B and L, but not the calpains or caspases, is effective at reducing infarct volume and improving functional scores when administered intravenously to rats after 2 hours of MCAO and reperfusion [12].…”
Section: Introductionmentioning
confidence: 99%
“…We did not detect labeled cells after hypoglycemic insult by using immunohistochemical probes of caspase and calpain pathways. However, these do not represent the only modes of neuron death as cathepsins are also implicated in neuron death, for example, after cerebral ischemia (Seyfried et al, 1997;Hill et al, 1997;Ü nal-Çevik et al, 2004). Because the number of dying cells is small in this model, it is not likely that methods for quantifying neuron loss (such as Nissl staining) will detect significant depletion of neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of cathepsin B in ischemic cell death has been demonstrated in mild models of transient focal (Seyfried et al, 1997) and global (Hill et al, 1997;Kohda et al, 1996;Yamashima et al, 1998) ischemia, where the protease participates to reperfusion-associated damage. Our results show that cathepsin B is also released from lysosomes in acute focal ischemia, in the absence of reperfusion, suggesting that lysosomal destabilization is part of the primary events that lead to cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%